Penambahan Urea atau DL-Metionina ke dalam Ransum Komplit Biomassa Ubi Jalar pada Kelinci - L Khotijah (Media Peternakan, 2006)
Twenty male cross-breed weanling rabbits were used to study the effect of urea or DL-methionine addition in sweet potatoes biomass complete diets. Completely randomized design was used in this experiment with four treatments and five replications. The treatments consisted of A (comercial diet); B (sweet potatoes biomass diet); BU (B + 0.5% urea) and BM (B + 0.5% DL-methionine). The dry matter intake, average daily gain (AVG), feed conversion ratio, dry matter and protein digestibility and nitrogen retention were measured in this experiment. The result showed that the treatments did not significantly affect dry matter intake and feed conversion ratio, digestibility of dry matter and protein, but supplementation of DL-methionine significantly affected average daily gain and nitrogen retention (P < 0.05). It was concluded that urea or DL-methionine supplementation in sweet potatoes biomass diets could support good performance of rabbits and it could be used as an alternative source of feed for rabbits. Key words : rabbit, sweet potatoes, urea, DL-methionine, performance